P157 GIANT PEDUNCULATED OESOPHAGEAL LIPOSARCOMAS: A CASE AND REVIEW OF RESECTION TECHNIQUES. (23rd November 2019) - Ng, Y Annalisa; Lee, June; Lin, Jinlin; Ching, Siok Siong; Wong, S Andrew
Abstract: Aim: Liposarcomas are rare causes of oesophageal tumours, accounting for <1% of tumours. We present a case of giant oesophageal liposarcoma with a discussion focusing on resection techniques. Background & Methods: A 54-year-old gentleman presented to the hospital with symptoms of anaemia and weight loss for 3 months. A CT scan and oesophagogastroduodenoscopy (OGD) showed a giant, pedunculated polyp extending from the cervical oesophagus to cardioesophageal junction (CEJ) with mucosal ulceration at its distal aspect. Endoscopic ultrasound (EUS) revealed a 24 x 6 cm submucosal pedunculated mass with lipomatous regions and core biopsy only showed rare groups of spindle cells with no malignancy. Resection was advised in view of occult bleeding from polyp and endoscopic resection was deemed unsuitable in view of a highly vascular stalk and large size of polyp. He underwent surgical resection via a left cervical oesophagostomy with gastrostomy for polyp retrieval. Final histology showed a dedifferentiated liposarcoma arising within a giant fibrovascular polyp. Results: Open surgery has classically been standard of treatment, but endoscopic resection is less morbid and invasive. Endoscopic techniques described include using a retraction suture followed by division of the polyp stalk using ultrasonic shears, using a snare, endoscopic submucosal dissection (ESD), and application of hemoclips following diathermy. In cases where endoscopic resection is not feasible, surgery such as oesophagostomy, oesophagectomy and laparotomy for resection and retrieval of the tumour have been described. Main reason for oesophagectomy was the presence of a submucosal (rather than polypoid, pedunculated) large tumour. For resection via oesophagostomy, stalk transection can be performed via stapling devices or suture ligation. Conclusion: Giant oesophageal liposarcomas are very rare tumours. Such tumours are usually polypoid, arising from a pedicle in the proximal oesophagus. Resection techniques have shifted from oesophagectomy to less invasive means such as endoscopic resection or oesophagostomy. Decision on type of resection technique depends on tumour characteristics and location; with the guiding principle being resection with clear margins in order to prevent local recurrence.